Recurrent and capital estimates for Ondo states 1969; 1995: summary of approved budget - Ondo State Government (Nigeria); Ondo State Government, Nigeria (Akure: Ondo State Government, Nigeria, 1969)
This is the approved estimates and budget for capital and recurrent expenditure in Ondo State, Nigeria for 1995.
lje 15/3/2019
Arch.
Keywords: Budget; Expenditures, Public; Ondo State (Nigeria); Nigeria